2007
DOI: 10.1080/02841860701317865
|View full text |Cite
|
Sign up to set email alerts
|

MRI demonstration of the effect of neoadjuvant radiotherapy on rectal carcinoma

Abstract: (2007) MRI demonstration of the effect of neoadjuvant radiotherapy on rectal carcinoma, Acta Oncologica, 46:7,[989][990][991][992][993][994][995]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Patients were selected for neoadjuvant treatment based on pretreatment MRI stage in all studies, except one , that used clinical fixity to select patients. All studies assessed response following long‐course neoadjuvant regimes, and one study additionally assessed response following short‐course radiotherapy . Three studies were performed on a 3‐Tesla (T) magnet , otherwise 1.0T and 1.5T strength magnets were used.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were selected for neoadjuvant treatment based on pretreatment MRI stage in all studies, except one , that used clinical fixity to select patients. All studies assessed response following long‐course neoadjuvant regimes, and one study additionally assessed response following short‐course radiotherapy . Three studies were performed on a 3‐Tesla (T) magnet , otherwise 1.0T and 1.5T strength magnets were used.…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, not entirely clear which staging (MRI1, MRI2 or postoperative histopathology) provides the best diagnostic and prognostic information. Though one study claims that MRI before treatment correlates better with prognosis and local recurrence than histopathology after preoperative treatment [104], the TNM staging after treatment still has prognostic value [105]. Unfortunately, as MRI2 is a relatively new concept its prognostic value has not been validated, especially because it is done only in a subset of patients and with different protocols.…”
Section: Tumour Status After Preoperative Treatmentmentioning
confidence: 99%
“…31,32 Surprisingly, T-stage downstaging was observed in the CR07 trial (or perhaps the arms were imbalanced at randomisation), 5 but overall, the Dutch TME trial found no significant difference in tumour node metastasis (TNM) classification between SCPRT and surgery alone groups 6,30 and so the aim of SCPRT is simply to reduce the risk of pelvic recurrence. Further extension of the interval following SCPRT to surgery of at least 6 weeks does demonstrate significant histopathogical response and downstaging.…”
Section: 24mentioning
confidence: 99%
“…[27][28][29] Although size may diminish, 30 no reduction in tumour or nodal classification is expected if the interval is less than 10 days. 31 Yet, some downstaging is observed if surgery is delayed for more than 10 days.…”
Section: 24mentioning
confidence: 99%